Arquitectura tradicional colombiana como sistema pasivo de aprovechamiento energético (2019)
The architectural tradition of Colombia contains a rich culture not only as a historical witness of a country but also reflects the essence of the principies of sustainability, especially in its residential character. AII these strategies were innate to the needs of its people who knew how to adapt to their natural environment while colonizing space. This act full of wisdom dating from the origin of vernacular housing had different responses according to the variety of existing in the country climates, however these responses were lost over time which leaves today's date countless projects climatic functional deficiencies which directly affects not only the comfort and well-being at its users, but also contributes in excess energy consumption. For these reasons this article proposes to analyze the adaptive capacity of traditional Colombian architecture and use it as a broad theoretical catalog of possibilities to confront the architectural and real estate world today.